(untitled) (KASBIT Business Journal, 2014)
The purpose of this research is to determine factors that influence employees’ training in an organization and how they affect organizational performance. Literature review revealed that training is one of key element that helps employees’ to acquire competence and confer motivation and satisfaction. Employees learn teamwork, flexibility, integrity and result oriented competencies through training. On the other hand, it also contributes positively towards enhancement of organizational performance along with other factors. Data was collected from two regions of National Bank of Pakistan at Karachi. Researcher used random sampling technique to gather responses from 119 respondents through questionnaire. Analysis was done by simple regression technique with ANOVA. The results of research have revealed that the factors of employee’s training have optimistic and significant impact on organization performance of National Bank of Pakistan.